Extracellular Vesicles in Joint Disease and Therapy - Boere, Janneke; Malda, Jos; van de Lest, Chris H. A.; van Weeren, P. René; Wauben, Marca H. M. (Frontiers in Immunology, 2018)
The use of extracellular vesicles (EVs) as a potential therapy is currently explored for different disease areas. When it comes to the treatment of joint diseases this approach is still in its infancy. As in joint diseases both inflammation and the associated articular tissue destruction are important factors, both the immune-suppressive and the regenerative properties of EVs are potentially advantageous characteristics for future therapy. There is, however, only limited knowledge on the basic features, such as numerical profile and function, of EVs in joint articular tissues in general and their linking medium, the synovial fluid, in particular. Further insight is urgently needed in order to appreciate the full potential of EVs and to exploit these in EV-mediated therapies. Physiologic joint homeostasis is a prerequisite for proper functioning of joints and we postulate that EVs play a key role in the regulation of joint homeostasis and hence can have an important function in re-establishing disturbed joint homeostasis, and, in parallel, in the regeneration of articular tissues. In this mini-review EVs in the joint are discussed from a historical perspective in both health and disease, including the potential niche for EVs in articular tissue regeneration. Finally, the use of MSC-derived EVs that is recently gaining ground is highlighted and recommendations are given for further EV research in this field.